Neurofibromatosis type ii : case reports - Silva, Miguel (2017)
Introduction: Neurofibromatosis type II is a rare genetic disorder with an autosomal dominant mode of transmission characterized by the growth of multiples benign tumors in the nervous system. There is a broad clinical spectrum known. Manifestations of the disease depends on the extension and the localization of the tumors, the most common complaints are hearing loss, tinnitus, loss of balance, focal neurological deficits and hydrocephalia.Aim: This paper presents three cases of neurofibromatosis type II in which inaugural manifestation was within the field of Otolaryngology. We pretend to call awareness of this syndrome within our field and review of literature.Material and Methods:In this paper, we present the last three patients diagnosed with neurofibromatosis type II in the department of Otolaryngology at University Hospital of Coimbra.Discussion: Neurofibromatosis type II is causes by a genetic mutation located on the long arm of chromosome 22. The mutated gene decrease the production or the function of a tumor suppressor peptide, merlin. Affected patients developed signs and symptoms secondary of dispersed benign tumors in the central nervous system, highlight by bilateral vestibular schwannoma. The diagnosis of neurofibromatosis type II requires a high index of suspicion due to the variability of clinical manifestation. In this article, we showed that the inaugural manifestation of this disease may be an ordinary sign and symptom found in otolaryngology clinic.Conclusion: Otolaryngologist is usually the first physician to detect clinical signs and symptoms of this disease, which lead to significant loss on quality of life and average life expectancy. It is important to include this disease in the differential diagnosis of unspecific dizziness accompanied by focal neurologic signs, asymmetric bilateral sensorineural hearing loss and bilateral sudden hearing loss.